FORMATION OF THE COMMERCIAL INFRASTRUCTURE OF THE EURASIAN ECONOMIC UNION’S COMMON POWER MARKET - M. Suyunchev; E. Tregubova; Ju. Sheval (Вестник университета)
The commercial infrastructure formation is a key challenge of creating a common electric power market for the Eurasian Economic Union member states (Russia, Belarus, Kazakhstan, Kyrgyzstan and Armenia) provided for in the Treaty on the Eurasian Economic Union. The comparative analysis of electricity trading arrangements in the Eurasian Economic Union states have been presented in the article. It has been shown, that there are notable differences between combined power markets of these group of states in terms of the organization of trade relations (participants, infrastructure services, rules on trade and pricing policies). It has been established, that only the characteristics of the Russian electric power market fully comply with the requirements of program documents for the Eurasian Economic Union common electric power market. The appropriate recommendations on measures to adapt the power markets of other Eurasian Economic Union States to these requirements have been given